Bougainvillea spectabilis Exhibits Antihyperglycemic and Antioxidant Activities in Experimental Diabetes. (July 2016) - Chauhan, Pratibha; Mahajan, Sunil; Kulshrestha, Archana; Shrivastava, Sadhana; Sharma, Bechan; Goswamy, H. M.; Prasad, G. B. K. S.
The study investigates the effects of aqueous extract of Bougainvillea spectabilis leaves on blood glucose, glycosylated hemoglobin, lipid profile, oxidative stress, and on DNA damage, if any, as well as on liver and kidney functions in streptozotocin-induced diabetes in Wistar rats. Daily administration of the aqueous extract of B spectabilis leaves for 28 days resulted in significant reduction in hyperglycemia and hyperlipidemia as evident from restoration of relevant biochemical markers following extract administration. The extract also exhibited significant antioxidant activity as evidenced from the enzymatic and nonenzymatic responses and DNA damage markers. The extract restored kidney and liver functions to normal and proved to be nontoxic. A marked improvement in the histological changes of tissues was also observed. The present study documented antihyperglycemic, antihyperlipidemic, and antioxidative potentials of the aqueous extract of B spectabilis leaves without any toxicity in streptozotocin-treated Wistar rats.